Intra-night optical flux and polarization variability of BL Lacertae during its 2020–2021 high state. Issue 2 (21st April 2023) - Bachev, Rumen; Tripathi, Tushar; Gupta, Alok C; Kushwaha, Pankaj; Strigachev, Anton; Kurtenkov, Alexander; Nikolov, Yanko; Boeva, Svetlana; Damljanovic, Goran; Vince, Oliver; Stojanovic, Milan; Kishore, Shubham; et al.
ABSTRACT: In this work, we report the presence of rapid intra-night optical variations in both flux and polarization of the blazar BL Lacertae during its unprecedented 2020–2021 high state of brightness. The object showed significant flux variability and some colour changes, but no firmly detectable time delays between the optical bands. The linear polarization was also highly variable in both polarization degree and angle (electric vector polarization angle). The object was observed from several observatories throughout the world, covering a total of almost 300 h during 66 nights. Based on our results, we suggest that the changing Doppler factor of an ensemble of independent emitting regions, travelling along a curved jet that at some point happens to be closely aligned with the line of sight, can successfully reproduce our observations during this outburst. This is one of the most extensive variability studies of the optical polarization of a blazar on intra-night time-scales.